Civil responsibility in Geriatric Psychiatry. Issue 5 (September 2021) - Vajawat, Bhavika; Hegde, Prakyath R.; Varshney, Prateek; Malathesh, Barikar C.; Kumar, Channaveerachari Naveen; Math, Suresh Bada
Mental health issues impair decision-making capacity, more so in elderly people. Impaired decision-making capacity can make person unfit to enter into various civil deeds and agreements. Such civil deeds can include guardianship, property transaction, holding a bank account, having voting rights, making a will, donating an organ, etc. This article focuses on importance of mental health in entering into above-mentioned civil agreements, how to do assessments to determine if one is fit to enter into civil agreements, and what are the legal ways in which a person can avail help to execute his/her civil rights even when affected by mental health issues.